THE PROBLEMS OF LAND DEGRADATION IN ALBANIA - Qamil Lireza; Linert Lireza (European Scientific Journal, ESJ, 2014)
In this article are treated the land degradation's problems. At thebeginning of the article are given the causes and factors that have promotedand developed the erosive-denuding processes, where are mentioned; thegeological construction, the typical Mediterranean climate, the poverty ofvegetation cover, typical mountainous landscape and anthropogenic factors.It is indicated the methodology used in the treatment of the article. Further, itis analyzed the current situation of degraded surfaces in Albania, which isexpressed in numbers, according to different periods. The erosion's intensityindicators are also reflected graphically. At the end of this article areprovided general conclusions and recommendations for anti-erosionmeasures to protect the land from erosion processes.